2005
DOI: 10.1002/ejic.200400925
|View full text |Cite
|
Sign up to set email alerts
|

Acidities of Nitrous and Nitric Acids

Abstract: The energies of nitrous and nitric acid and their anions were calculated at the MP2(FC)/6-311++G(2d,2p) level. Their acidity was related to the acidity of hydroxylamine derivatives using isodesmic reactions. This procedure reveals that the molecules of HNO 2 and HNO 3 are strongly stabilized (by 119 or 206 kJ·mol -1 , respectively) but their anions are stabilized even more (by 282 or 428 kJ·mol -1 ). The acidity of these acids is thus caused by the low energy of their anions and not by the high energy of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[55] In recent years many research groups have pursued the goal of explaining the nature of substituent effect by means of theoretical calculations. In a series of papers, Exner group www.interscience.wiley.com/journal/poc focused on field-inductive effect [34,[56][57][58][59][60] reasoning that discussion: 'whether the electronic transmission is through space or through bonds' , is meaningless, and that although the effects are mainly electrostatic in nature (in the sense of multipole expansion), the EN component can be separated and can play a substantial role. Exner et al [61][62][63][64][65] also devoted several computational papers to resonance effect and to EN itself.…”
Section: Introductionmentioning
confidence: 99%
“…[55] In recent years many research groups have pursued the goal of explaining the nature of substituent effect by means of theoretical calculations. In a series of papers, Exner group www.interscience.wiley.com/journal/poc focused on field-inductive effect [34,[56][57][58][59][60] reasoning that discussion: 'whether the electronic transmission is through space or through bonds' , is meaningless, and that although the effects are mainly electrostatic in nature (in the sense of multipole expansion), the EN component can be separated and can play a substantial role. Exner et al [61][62][63][64][65] also devoted several computational papers to resonance effect and to EN itself.…”
Section: Introductionmentioning
confidence: 99%
“…Exner and B€ ohm carried out a number of density functional calculations on various organic compounds and validated the concept of Hammett constant. [29,30,36,37] In the case of fulvenes, a study suggested that the lowest electronic states of fulvene can be varied with substituents. [12] Oziminski and Krygowsky interposed a correlation between p-electron population at carbon atoms of the ring in fulvene and benzene with substituent constant and with aromaticity index NICS.…”
Section: Introductionmentioning
confidence: 99%